PENGARUH LATIHAN SCISSOR JUMPS TERHADAP POWER OTOT TUNGKAI PADA OLAHRAGA PENCAK SILAT PUTRI PERGURUAN PENCAK SILAT TANGAN MAS PEKANBARU - Minal Uyun; Ramadi Ramadi; Aref Vai (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research is done to find out if there is any effect of Scissor jumps training on leg muscle power Pencak Silat sport female Pencak Silat Tangan Mas Pekanbaru. So that at the time of the championships the female athletes of Tangan Mas still has a shortage of Power in kicks. Kicks done by the female athletes of Tangan Mas can still be easily avoided and foiled by opponents. This is due to legs muscle Power on the female athletes pencak Silat Tangan Mas Pekanbaru is still lacking. This form of research is research with experimental treatment (experimental), With a population of the female athletes of Pencak Silat tangan mas Pekanbaru, The data in this research is the whole active female athlete of Pencak Silat tangan mas that amounted to 6 people. The instrumen performed in this research is by using Vertical Jump Test which aims to measure the Power of legs muscle. Afterward, the data is processed with statistics, to test the normality with the lilliefors test at a significant level of ∝ 0.05. Hypothesis proposed is the effect of Scissor jumps training on leg muscle power in Pencak Silat sport female pencak silat Tangan Mas Pekanbaru. Based on test analysis t produces Tcount of 11,111 and Ttable 2.015 which means Tcount > Ttable. Based on the analysis of statistical data, there is an average Pre-Test 28,33 and the average post-test of 32,33, then the data is normal. Thus, it can be concluded that there is the effect of scissor jumps training on leg muscle power in pencak Silat sport female pencak silat TanganMas Pekanbaru.Key Words: Scissor Jump, Leg Muscle Power